2017
DOI: 10.7759/cureus.1669
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Infant Mortality Trends in Qatar from 2004 to 2014

Abstract: BackgroundInfant mortality is an important health indicator that estimates population well-being. Infant mortality has declined globally but is still a major public health challenge. This article provides the characteristics, causes, burden, and trends of infant mortality in Qatar.MethodsFrequencies, percentages, and rates were calculated using data from birth-death registries over 2004–2014 to describe infant mortality by nationality, gender, and age group. We calculated the relative risks of the top causes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Age-specific mortality rates in Qatari and non-Qatari children were closer in this study compared to adults. A previous study showed marginally less infant mortality rates in Qataris compared to non-Qataris in the period of 2004–2014 (relative risk of mortality: 0.81, 95% confidence interval: 0.66–1.00) ( 24 ), however, our findings did not support it.…”
Section: Discussioncontrasting
confidence: 99%
“…Age-specific mortality rates in Qatari and non-Qatari children were closer in this study compared to adults. A previous study showed marginally less infant mortality rates in Qataris compared to non-Qataris in the period of 2004–2014 (relative risk of mortality: 0.81, 95% confidence interval: 0.66–1.00) ( 24 ), however, our findings did not support it.…”
Section: Discussioncontrasting
confidence: 99%
“…Causes of death were coded in accordance with the International Classification of Diseases guidelines (ICD-10, Version 2016). The detailed process of data collection and “cause of death” coding was described elsewhere 7. The data contained information on date, place, and cause of death, as well as included demographic information like sex, age, and nationality (Qatari or non-Qatari) 7…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we aimed to investigate the trends in childhood mortality and the leading causes of death by nationality and sex in Qatar from 2004 to 2016. The mortality trends and characteristics among infants under one year of age in Qatar have already been discussed in our previous publication 7…”
Section: Introductionmentioning
confidence: 97%
“…Qatar ranks 16th globally in this report 5 . CAs are the leading cause of infant mortality in the country, accounting for 34.5% of total infant mortality 8 . CAs are estimated to comprise 2.13% of total deaths, with an age-adjusted death rate of approximately 4.95 per 100,000 of population 9 .…”
Section: Introductionmentioning
confidence: 99%